Formulation for the Performance Analysis of a Lithium-Carbon Monofluoride Cell - Sandhu, Sarwan S. (RA Journal Of Applied Research, 2023)
The formulation presented in this paper is for the performance analysis of a primary lithium-carbon monofluoride cell. The formulation can also be used to compute the theoretical cell open-circuit voltage; the fractional conversion of the limiting reactant, carbon monofluoride and hence, the cell fractional state-of-charge; total amount of charge required to be involved for the complete utilization of the cell cathode active material, carbon monofluoride as well as the transient specific amount of charge involved; the ratio of the thermal energy production to the electric energy production; and the rate of heat exchange between the cell exterior surface and its surroundings required for the determination of the cell average temperature.